The Patron-Client Relationship in Senangin (Eleutheronema tetradactylum) Fishery: A Case Study of Fishermen and Tauke (Capital Owners) in Rokan Hilir, Riau, Indonesia (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
This study aims to analyze the pattern of patron-client relationships between senangin (Eleutheronema tetradactylum) fishermen and tauke (capital owners) in Rokan Hilir Regency, Riau Province, Indonesia. The research employed a qualitative approach using primary data obtained through direct interviews with fishermen, tauke, and related stakeholders, and secondary data collected from government institutions and statistical reports. The findings reveal that fishermen depend heavily on tauke due to limited capital and restricted market access. Tauke provides fishing facilities, such as operational costs, boats, and fishing gear, while fishermen are bound to sell their catches exclusively to the tauke. This relationship includes both economic aspects (capital support and profit-sharing system, with 75% of catches going to fishermen and 25% to tauke) and non-economic aspects (loans during lean seasons, assistance in emergencies, trust, and loyalty). The study concludes that the patron-client relationship forms a reciprocal yet asymmetric dependency, where fishermen gain access to capital and markets, while tauke maintains control over fish pricing and distribution. Institutional strengthening and alternative financial mechanisms are recommended to reduce fishermen’s dependency and promote sustainable fisheries management.